Treatment of Stage I-III Hip Joint Tuberculosis With Open Surgical Debridement and Hip Spica in Children: A Retrospective Study. Issue 9 (9th October 2022) - Yang, Lei; Zuo, Jingjing; Li, Lang; Wang, Daoxi; Yang, Xiaodong; Tang, Xueyang
Abstract : Background: This study aimed to evaluate the outcome of surgical debridement combined with postoperative hip spica immobilization in the treatment of hip joint tuberculosis in children. Methods: This retrospective study enrolled 87 children with stage I to III hip joint tuberculosis treated surgically at our hospital from January 2010 to January 2016. All patients considering hip tuberculosis routinely received a 4-week conservative treatment first, including rest, protected weight-bearing, and 4-drugs antitubercular chemotherapy. Surgical debridement was indicated when there was no relief after this conservative protocol. Patients were divided into 2 groups according to the duration of hip spica immobilization after operation: group A (hip spica for 4 wk, 39 patients) and group B (hip spica for 6 wk, 48 patients). All patients were recommended partial weight-bearing for 7 days and then followed the same hip joint exercises program when spica was removed. Postoperative radiographs, hip dislocation or subluxation, and modified Harris hip score (MHHS) were assessed. All patients were followed up at least 5 years. Results: There were 87 patients enrolled in our study, including 34 females and 53 males, with a mean age of 7.2±2.8 years old (range: 2 to 14 y). No significant difference was observed between these 2 groups in baseline data. In group A, the mean MHHS improved from 52.1±14.7 before surgery to 87.8±8.3 at the final follow-up ( P <0.000). In group B, there was also a significant difference between the preoperative MHHS (52.7±9.4) and the final MHHS (88.6±6.5) ( P <0.000). Although there was no significant difference between these 2 groups in the final MHHS ( P =0.593), there were also no significant differences between these 2 groups in wound healing delay (3 in group A and 6 in group B, P =0.705) and pathologic subluxation (3 in group A and 1 in group B, P =0.467). The only difference between group A (79.2±8.5) and group B (75.5±7.5) was the early functional outcome assessed by using MHHS after 1 month of hip joint exercises ( P =0.032). Conclusions: Surgical debridement combined with antitubercular chemotherapy is an effective treatment for stage I to III hip tuberculosis in children when there is no improvement after conservative treatment. Prolonged hip spica immobilization may not reduce the risk of hip subluxation after open surgical debridement but could lead to a delay in early functional recovery. Time of spica immobilization should be individualized and based on the surgeon's evaluation and the patient's condition.